Prevalence and risk factors for painful diabetic peripheral neuropathy: a systematic review and meta-analysis - Peng Zhou; Jin song Zhou; Jin song Zhou; Jin song Zhou; Jin jie Li; Jin jie Li; Jin jie Li; Lang Qin; Wen feng Hu; Xiao yi Zhang; Jian xia Wang; Jian xia Wang; et al. (Frontiers in Neurology)
ObjectiveThis study aimed to explore the prevalence and risk factors for painful diabetic peripheral neuropathy through meta-analysis, and to provide countermeasures for early intervention and active prevention of diabetic peripheral neuropathic pain.MethodsWe conducted a systematic search of PubMed, Embase, Web of Science, and Cochrane Library for articles published from the establishment of the database to November 2024. A total of 14 studies (nine cross-sectional studies and five cohort studies) qualified for meta-analysis. We used a random-effects meta-analysis and assessed heterogeneity and publication bias.ResultsA total of 14 studies (nine cross-sectional, five cohort) were included. The prevalence of PDPN was estimated at 33.9% (95% CI [19.4%−48.5%]). Significant risk factors included female gender (OR = 1.29, P = 0.004), glycosylated hemoglobin levels (WMD = 0.14, P < 0.001), nephropathy (OR = 1.41, P < 0.001), retinopathy (OR = 1.32, P = 0.040), cardiovascular disease (OR = 1.46, P < 0.001), arterial hypertension (OR = 1.25, P = 0.047), triglycerides levels (WMD = −0.10, P < 0.001), low density lipoprotein levels (WMD = −0.20, 1. 0.001), smoking (OR = 0.90, P = 0.001), drinking alcohol (OR = 0.87, P = 0.001), glomerular filtration rate levels (WMD = −7.11, P < 0.001), obesity (OR = 2.00, P = 0.001). The multivariate analysis results showed that female gender (OR = 1.42, P = 0.032), age of onset (OR = 1.19, P < 0.001), duration of diabetes (OR = 1.29, P < 0.001), and retinopathy (OR = 1.90, P = 0.032) were indicated as risk factors for painful diabetic peripheral neuropathy.ConclusionThis meta-analysis suggests that female gender, glycosylated hemoglobin levels, nephropathy, retinopathy, cardiovascular disease, arterial hypertension, smoking, drinking alcohol, glomerular filtration rate levels, obesity, age of onset and duration of diabetes are indicated as risk factors for painful diabetic peripheral neuropathy in diabetic patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42025629060.